Modelling and verification of hybrid electric propulsion system - Ng, Marcus Jun Jie (Nanyang Technological University, 2021)
Increasing climate concerns stemming from conventional fossil fuel sources has shifted focus to electric and hybrid electric engines. There have been on-going research and development of electric aircraft. However, due to the low energy density of the current battery technology, hybrid-electric propulsion systems have gathered interest as they attempt to harness the benefits of two or more distinct power sources. System architecture, configuration and control strategies are paramount to Hybrid Electric Propulsion Systems (HEPS). This project aims to verify the viability of a modified parallel HEPS. A MATLAB Simulink model of the system is created to replicate the major power generating components namely, the internal combustion engine, direct current generator, and the battery. Mathematical equations and equivalent circuit models were implemented in the simulator. To verify the accuracy of the simulator, a series of physical experiments were conducted. The physical experiments used commercial off the shelf items and verified that power combination of two distinct power source, validating the simulation model. The viability of the modified parallel HEPS was applied to an unmanned aerial vehicle (UAV) model to demonstrate extended flight endurance and fuel savings in the simulator.